2012
DOI: 10.1371/journal.pone.0050040
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone Reinstates Tyrosine Hydroxylase Immunoreactive Neurons and Motor Performance in an MPTP-Lesioned Mouse Model of Parkinson's Disease

Abstract: Restorative/protective therapies to restore dopamine neurons in the substantia nigra pars compacta (SNpc) are greatly needed to effectively change the debilitating course of Parkinson's disease. In this study, we tested the therapeutic potential of a neurogenic neurosteroid, allopregnanolone, in the restoration of the components of the nigrostriatal pathway in MPTP-lesioned mice by measuring striatal dopamine levels, total and tyrosine hydroxylase immunoreactive neuron numbers and BrdU-positive cells in the SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 65 publications
3
44
0
Order By: Relevance
“…In support of the role of PROG metabolites in neuroprotection, several in vitro and in vivo studies have shown that blockage of 5α-reductase, the first enzyme involved in the conversion of PROG into DHP, abolishes the neuroprotective effect of PROG in various models [50,51,52]. Furthermore, administration of THP once weekly for 2 weeks to MPTP-treated mice is reported to restore positive cells for tyrosine hydroxylase in the substantia nigra as well as motor behavior, and to induce the generation of new positive neurons for tyrosine hydroxylase in the substantia nigra [53]. In this study, THP was administered at a time when the damage induced by MPTP is stable, that is after 7 days [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of the role of PROG metabolites in neuroprotection, several in vitro and in vivo studies have shown that blockage of 5α-reductase, the first enzyme involved in the conversion of PROG into DHP, abolishes the neuroprotective effect of PROG in various models [50,51,52]. Furthermore, administration of THP once weekly for 2 weeks to MPTP-treated mice is reported to restore positive cells for tyrosine hydroxylase in the substantia nigra as well as motor behavior, and to induce the generation of new positive neurons for tyrosine hydroxylase in the substantia nigra [53]. In this study, THP was administered at a time when the damage induced by MPTP is stable, that is after 7 days [54].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an alteration in PROG metabolism has also been reported in a different animal model of PD [58]. Further work is needed to investigate how the decrease in PROG metabolites contributes to the degenerative process, but current data suggest that PROG could be an interesting therapeutic compound, since THP is known to modulate dopaminergic systems, to act as a positive neuromodulator of GABA A receptors, and to have neuroprotective effects [53,59]. Future studies that compare the neuroprotective effect of PROG and THP on dopaminergic neurons could also be very informative, as THP could potentially be used instead of PROG when 5α-reductase activity is impaired, as has been observed to occur in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unbiased Stereology-The stereology was performed as described previously (26). Briefly, montage images of all sections that contain the hippocampus were captured using a 3i microscope with Slidebook 5.5 software (Intelligent Imaging Innovations, Inc, Denver, CO).…”
Section: Methodsmentioning
confidence: 99%
“…Allopregnanolone, a metabolite of progesterone produced by astrocytes within the CNS, is selectively enriched in the SN of post-mortem brains of healthy individuals (Bixo et al 1997), and has been shown dramatically reduced not only in brains of PD patients, but also in 6-OHDA lesioned rats (Luchetti et al 2010;Melcangi et al 2012). Interestingly, systemic administration of allopregnanolone into MPTPintoxicated mice promotes restoration of dopaminergic neurons in the SN and improves motor performance of these mice (Adeosun et al 2012). Considering this data, it is possible to speculate that increased GABA detected during PD might work initially counteracting inflammatory function mediated by pathogenic encephalitogenic CD4+ T-cells and M1-like microglia, nevertheless, this beneficial effect might be lost once the concentration of positive regulators of GABA signalling is significantly reduced upon PD (Fig.…”
Section: Neurotransmitters As Modulators Of Encephalitogenic T-cells mentioning
confidence: 99%